Benefit and risk of adding rivaroxaban in patients with coronary artery disease: A systematic review and meta‐analysis. Issue 1 (21st November 2020) - Xie, Cheng; Hang, Yongfu; Zhu, Jianguo; Li, Caiyun; Jiang, Bin; Zhang, Yuzhen; Miao, Liyan
Abstract: Background: Although the European Medicines Agency and the US Food and Drug Administration have, respectively, approved rivaroxaban for the prevention of recurrent major adverse cardiovascular events in patients with myocardial infarction and stable coronary artery disease, its efficacy and safety is unclear. This meta‐analysis aimed to evaluate the benefit and risk of adding rivaroxaban in coronary artery disease (CAD) patients, focusing on treatment effects stratified by different baseline clinical presentations. Hypothesis: There are differences in treatment effects of adding rivaroxaban among CAD patients with different baseline clinical presentations. Methods: Medline, EMBASE, and Cochrane Databases were systematically searched from inception to 21 July 2020 for randomized controlled trials (RCTs) comparing rivaroxaban in CAD patients. The primary efficacy endpoint and safety endpoint were assessed by using Mantel–Haenszel pooled risk ratios (RRs) and 95% confidence intervals (CIs). Results: Five RCTs that included 43 650 patients were identified. Patients receiving rivaroxaban had a significantly lower risk of the primary efficacy endpoint (RR, 0.86; 95% CI, 0.76–0.97, p = .01) accompanied by increased risk of the primary safety endpoint (RR, 1.83; 95% CI, 1.10–3.05, p = .02). Subgroup analyses showed that in males the risk–benefit appears to be more favorable while in patients ≥65 years, in females, in patients with diabetes, those with mild to moderate impaired renal function, and region of Asia/other seems unfavorable. Conclusion: Rivaroxaban may provide an additional choice for secondary prevention in CAD patients. However, careful estimation of the risk of ischemic and bleeding events using patient characteristics are critical to achieving net benefit.